Implementasi Prinsip Ultimum Remedium Terhadap Keterlanjuran Kegiatan Perkebunan Kelapa Sawit di Dalam Kawasan Hutan Berdasarkan Undang-Undang Cipta Kerja - Syafira Almutahaliya (Fakultas Hukum Universitas Andalas, 2024)
The provision in Article 37 number 20 of the Cipta Kerja, regulates the Ultimum Remedium Principle against the continuation of oil palm plantation activities which is reflected in the insertion of Articles 110A and 110B between Article 110 and Article 111 of Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction. This research will answer the problem of how the implementation of the Ultimum Remedium Principle against the continuation of oil palm plantation activities in forest areas based on the Job Creation Law and how are the obstacles in the Implementation of the Ultimum Remedium Principle against the continuation of oil palm plantation activities in forest areas by the West Sumatra Provincial Forestry Service. The research method used is empirical legal research using primary data obtained by interviewing the Forest Damage Control and Security Section in the Forest Protection and Conservation of Natural Resources and Ecosystems Division of the West Sumatra Provincial Office. Based on the results of the research, the application of the ultimum remedium principle to the continuation of oil palm plantation activities in forest areas is resolved by applying for a permit by paying forest resource provisions and reforestation funds to the state treasury. Then for everyone who lives around or in the forest area for five consecutive years, can be subject to exclusion or maximum subject to administrative sanctions in the form of temporary suspension of business activities, payment of administrative fines or government coercion. Then the obstacles to the implementation of the ultimum remedium principle against the continuation of oil palm plantation activities in forest areas are in the form of technical problems in the field such as, lack of public understanding, uncooperativeness of authorized officials, and misappropriation by law enforcement officers.